Reading Aloud and Small Group Discussion: A Comparative Study of Reading Strategies - Dyah Esti Handayani; Abdul Ngafif; Sri Widodo (Scripta : English Department Journal, 2020)
One of the fundamental problems in teaching is closely related to teaching strategy. This basic problem comes to almost all subjects in senior high school included English in which more to teaching reading than other language skill. This fundamental problem then leads the researchers to do research which goal is to find out whether reading aloud or small group discussion more effective in teaching reading for senior high school. By applying causal-comparative research, the researchers did research in SMAN 7 Purworejo. Employing Class XI MIPA 5 taught using reading aloud strategy and Class XI MIPA 6 taught using small group discussion, the researchers then give 25 questions of a multiple-choice test to evaluate the result of teaching reading. The result of this research shows that the mean score of XI MIPA 5 is 88.97 and the mean of XI MIPA 6 is 89.14 which means that both of the classes have similar competencies in reading. Then, from the computation of inferential analysis, it shows that the result of Zvalue (1.503) is lower than Ztable (1.96). From the result, it can be concluded that both of the strategies have equal power to be used in teaching reading.